2019
DOI: 10.3390/molecules24234295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blackcurrant Anthocyanin on Endothelial Function and Peripheral Temperature in Young Smokers

Abstract: Background: Blackcurrant anthocyanin (BCA) is expected to repair endothelial dysfunction, but it remains unclear whether beneficial effects are present in young healthy persons. This study examines whether supplements containing blackcurrant anthocyanin improve endothelial function and peripheral temperature in young smokers. Methods: Young, healthy male nonsmokers (N group: n = 11; mean age 22 ± 2 years) and smokers (S group: n = 13; mean age 21 ± 1 years) were enrolled. A randomized and double-blind trial wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…; 2 -L-dehydroascorbic acid (DHA), L-ascorbic acid (ASC), mg/100 g f.w. ; 3 -values in the same column followed by different letters (a-c) are significantly different at 5% level of probability, with "a" always representing the highest value; 4 -not significant (NS).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; 2 -L-dehydroascorbic acid (DHA), L-ascorbic acid (ASC), mg/100 g f.w. ; 3 -values in the same column followed by different letters (a-c) are significantly different at 5% level of probability, with "a" always representing the highest value; 4 -not significant (NS).…”
Section: Discussionmentioning
confidence: 98%
“…Oxidative stress is one of the early civilization diseases, where uncontrolled negative forms and free radicals affect the reduced mechanisms of cell control. The state of increased oxidative stress is observed in the course of inflammatory diseases and in smokers [4]. The flavonoid group is also attributed with positive effects on the cardiovascular system, mainly caused by quercetin and rutin.…”
Section: Introductionmentioning
confidence: 99%
“…BCE strongly increased endothelial nitric oxide synthase ( eNOS ) mRNA expression and nitric oxide production in human endothelial cells, and dietary BCE increased eNOS protein expression in an OVX rat model [ 17 ]. Additionally, BCE effectively prevented lipid-associated metabolic abnormalities [ 18 ] and attenuated smoking-induced acute endothelial dysfunction and improved peripheral temperature in young smokers [ 55 ]. Furthermore, the amount of BCE administered in the animal model in the current study was equivalent to the daily dose of polyphenols (1.9 g/60 kg body weight) provided by BCE (5.1 g) previously administered to humans [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the other studies, all carried out in healthy men, all tested concentrations increased FMD [ 29 , 46 , 66 ]. However, Tomisawa et al [ 69 ] reported that FMD remained unchanged after a blackcurrant intervention in young male smokers.…”
Section: Resultsmentioning
confidence: 99%